Infecções hospitalares por Enterobacteriaceae produtora de β-lactamase de amplo espectro (ESBL): ocorrência e preditores de mortalidade em um hospital universitário mineiro - Moreira, Ana Paula Amâncio (2011)
Introduction: The emergence of resistant bacteria in the etiology of infections in hospitals is more significant in developing countries due to lack of human and financial resources, lack of microbiological diagnosis resulting in inadequate empirical antimicrobial therapy. Objectives: This study aimed to evaluate the occurrence of nosocomial infections ESBL-producing Enterobacteriaceae among third-generation cephalosporin-resistant isolates and to identify predictors of hospital mortality among these patients. Methods: We conducted a prospective cohort study to analyze predictors of mortality in patients with nosocomial infections by ESBL-producing Enterobacteriaceae from June 2009 to March 2010 at Hospital de Clínicas da Universidade Federal de Uberlândia (HC-UFU). The active surveillance was carried out by regular visits to the laboratory of HC-UFU for detection of third generation cephalosporins resistant, ESBL-producing or non ESBL-producing. The identification of samples, antibiotic susceptibility test and ESBL phenotypic test were performed using the automated system Vitek ® 2. Demographic and clinical data and other risk factors were obtained from patient charts and evaluated by univariate and multivariate statistical analysis. Survival curves were prepared using Kaplan-Meier estimation to compare the hospital mortality (30 days) between ESBL and non-ESBL infections. The study was approved by the Ethics Committee. Results: Overall, 184 (10.3%) patients were diagnosed with nosocomial infection by third generation cephalosporin resistant Enterobacteriaceae, mostly (65.2%) caused by ESBL producing strains, belonging to the species K. pneumoniae (67.5%) and E. coli (31.6%). The most frequent infections with these microorganisms were the urinary tract (39.1%) and bloodstream (31.6%) and hospital mortality rate was significantly higher in the ESBL group. Variables that independently predict death by multivariate analysis consist of malignancies (OR 7.86; 95% CI 2.25-27.49; P= 0.001) and inappropriate empirical therapy (OR 2.92; 95% CI 1.13-7.52; P= 0.02). Conclusion: Hospital infections by third generation cephalosporin resistant Enterobacteriaceae are endemic in this hospital, mostly represented by samples of ESBL producing K. pneumoniae and E. coli. Malignancies and inappropriate empirical therapy were independent prognostic factors for hospital mortality. Overall, the observed mortality in this group was high and significantly higher than non-ESBL group.